Evaluation of Growth Performance of 55 Progenies of Acacia nilotica Willd. and their Conservation in Field Gene Bank at Bir Bhadson, Patiala (Punjab), India - Ayoub Dar, Md.; Nautiyal, S.; Mishra, Ashutosh; Nautiyal, D. P. (Indian Forester, 2009)
Field gene bank of Acacia nilotica of 55 progenies has been established and maintained at Bir Bhadsun (Punjab) for conservation and future breeding programme. Seeds were collected from all 55 progenies of 9 provenances of three states viz., Punjab, Haryana, and Himachal Pradesh covering its natural distribution zone. Seeds were sun dried and their characters (seed length, seed width and seed thickness) were measured. Maximum and minimum seed length, seed width and seed thickness were obtained from Fatehgarh Sahib, Punjab Provenance respectively. Seeds were sown in the trays at Plant Physiology Nursery, Forest Research Institute, Dehra Dun. The highest germination percentage has been found in Pinjore Road, Haryana provenance. After germination the seedlings were shifted in the polybags filled with sand, soil and farmyard manure in 2:1:1 ratio and kept in the nursery for growth. After one year the seedlings of all the 55 progenies were then transplanted in the field at Bir Bhadsan (Patiala, Punjab) in about 2 ha land following Randomized Block Design (simple pair design ). The data on growth and survival were recorded at the six month and five year old seedlings after transplanting in the field. Significant variation was observed among all the progenies of all observed characters. The best average growth (after six months of planting) was observed in the Roop Nagar (Punjab), progenies whereas, minimum growth was observed in the progenies of Bhadsun Nabha Road (Punjab). However, the maximum average growth (after five years of planting) was observed in the Kurali Naraingarh (Punjab), Pinjore Road (Haryana), and the minimum was observed in the progenies of Rajpura (Himachal) and Nalagarh Road (H.P.).